2010
DOI: 10.1007/s00204-010-0521-0
|View full text |Cite
|
Sign up to set email alerts
|

The toxicokinetics of ketoprofen in Gyps coprotheres: toxicity due to zero-order metabolism

Abstract: In a safety study, Cape GriVon vultures (Gyps coprotheres) were dosed with ketoprofen at single doses of »1 mg/kg (n = 5) and 5 mg/kg (n = 11). No toxicity was reported in the 1 mg/kg group, with the AUC inf , V z and Cl being 10.42 g/ml h, 0.37 l/kg and 0.10 l/h kg, respectively. Toxicity occurred in the 5 mg/kg group, with 7 of the 11 birds dying. Clinical signs of toxicity included depression, loss of appetite and apparent coma. Animals died within 48 h of dosing. The AUC inf , V z and Cl in the birds that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…This once again supported previous findings that toxicity is related to zero-order metabolism. In addition, the increase in the AUC last and C max also indicated that toxicity resulted in saturation of presystemic elimination pathways [64].…”
Section: In Vivo Approaches In Studying Comparative Metabolismmentioning
confidence: 99%
“…This once again supported previous findings that toxicity is related to zero-order metabolism. In addition, the increase in the AUC last and C max also indicated that toxicity resulted in saturation of presystemic elimination pathways [64].…”
Section: In Vivo Approaches In Studying Comparative Metabolismmentioning
confidence: 99%
“…While models are also available for uptake and metabolism, understanding inter- and intraspecies variation is fundamental to predicting toxicity. Experiments by Vinny Naidoo (University of Pretoria) have shown that Gyps and other vulture species have an unusual metabolism with respect to NSAIDs [16]; they are suggested to be CYP 2C9 deficient or diminished, as are cats, which are also highly sensitive to NSAIDs and so may provide a pharmacokinetic model for vultures.…”
Section: Behaviour Of Pharmaceuticalsmentioning
confidence: 99%
“…Generally speaking, far more information is urgently needed regarding NSAIDs known or suspected to cause gout-related mortality (e.g. carprofen, ibuprofen, ketoprofen, flunixin, phenylbutazone) [112][113][114], no less so now that diclofenac has been registered for veterinary use in some parts of Europe, especially Spain. This will entail assessing the disposition of these agents in a relevant suite of agricultural animals, conducting safety trials with vultures (or a vulture cell line) and actively monitoring for residue levels in livestock carcasses.…”
Section: The Situation In the European Unionmentioning
confidence: 99%